A First Look at the Terminal Pleistocene/Early Holocene Record of Guano Valley, Oregon, USA. (3rd April 2018) - Reaux, Derek J.; Smith, Geoffrey M.; Adams, Kenneth D.; Jamaldin, Sophia; George, Nicole D.; Mohr, Katelyn; Rosencrance, Richard L.
ABSTRACT: Surface sites play a vital role in interpreting terminal Pleistocene/early Holocene (TP/EH) lifeways in the Great Basin. Two years of work in Oregon's Guano Valley by crews from the University of Nevada, Reno have revealed a rich record of Western Stemmed Tradition occupations associated with an extensive delta system that brought freshwater into the valley from the adjacent tablelands. To date, we have recorded nearly 700 diagnostic TP/EH artifacts within the relatively small delta, making it one of the densest concentrations of Paleoindian artifacts in the region. This paper presents preliminary results from our archaeological and geomorphological investigations in Guano Valley as well as an extensive toolstone source provenance analysis.